1977
DOI: 10.1002/ijc.2910200506
|View full text |Cite
|
Sign up to set email alerts
|

Latent carcinoma of prostate at autopsy in seven areas. Collaborative study organized by the International Agency for Research on Cancer, Lyons, France

Abstract: A world-wide comparative study of the frequency and characteristics of latent carcinoma of the prostate was undertaken in seven areas, using standardized methods and "blind" microscopic evaluation in order to reduce selection and observer bias. The morphological features of 350 latent carcinomas found in 1,327 prostates were examined. Two Chinese populations, from Hong Kong and Singapore, showed a low frequency of latent carcinoma in comparison with western Europeans in Sweden and the Federal Republic of Germa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
116
0
16

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 532 publications
(140 citation statements)
references
References 17 publications
8
116
0
16
Order By: Relevance
“…1 The American Cancer Society estimates that there will be 230 110 new cases of CaP and 29 900 CaP deaths in the US in 2004. 2 However, little is known about the causes of the disease, the only established risk factors being age, 1 ethnicity/geographical location (eg, Japanese-Americans have a higher risk than native Japanese) [3][4][5] and family history. [6][7][8] Hormones are necessary for the growth and development of the prostate gland and have been implicated in the development of CaP.…”
Section: Introductionmentioning
confidence: 99%
“…1 The American Cancer Society estimates that there will be 230 110 new cases of CaP and 29 900 CaP deaths in the US in 2004. 2 However, little is known about the causes of the disease, the only established risk factors being age, 1 ethnicity/geographical location (eg, Japanese-Americans have a higher risk than native Japanese) [3][4][5] and family history. [6][7][8] Hormones are necessary for the growth and development of the prostate gland and have been implicated in the development of CaP.…”
Section: Introductionmentioning
confidence: 99%
“…7 The incidence of clinically significant disease varies markedly according to geography and ethnicity. Migration studies have shown that men from countries of low incidence assume the incidence of the adopted country after about 25 years especially after exposure to a western lifestyle, thus inferring an environmental causal component in transformation of latent into clinically significant cancer.…”
Section: Prostate Cancermentioning
confidence: 99%
“…Autopsy studies of Chinese's, German, Israeli, Jamaican, Swedish, and Ugandan men who died of other causes have found prostate cancer in 30% of men in their 50s, and in 80% of men in their 70s 2 . Men whom have first degree family members with prostate cancer appear to have doubled the risk of getting and disease compared to men without prostate cancer in the family 3 . This risk appears to be grater for men with an affected brother than for men with an affected father.…”
mentioning
confidence: 95%